Shadow IT and Business-Managed IT: A Conceptual Framework and Empirical Illustration - Kooper, Andreas; Furstenau, Daniel; Zimmermann, Stephan; Klotz, Stefan; Rentrop, Christopher; Rothe, Hannes; Strahringer, Susanne; Westner, Markus (International Journal of IT/Business Alignment and Governance (IJITBAG), 2018)
Research on Shadow IT is facing a conceptual dilemma in cases where previously “covert” systems developed by business entities are integrated in the organizational IT management. These systems become visible, are thus not “in the shadows” anymore, and subsequently do not fit to existing definitions of Shadow IT. Practice shows that some information systems share characteristics of Shadow IT but are created openly in alignment with the IT organization. This paper proposes the term “Business-managed IT” to describe “overt” information systems developed or managed by business entities and distinguishes it from Shadow IT by illustrating case vignettes. Accordingly, our contribution is to suggest a concept and its delineation against other concepts. In this way, IS researchers interested in IT originated from or maintained by business entities can construct theories with a wider scope of application that are at the same time more specific to practical problems. In addition, the terminology allows to value potentially innovative developments by business entities more adequately.